(untitled) (Global Journal of Science Frontier Research, 2015)
This study focus on High Energy K X-ray satellites which are a particular category of characteristic X-ray. They are emitted when an atom that has undergone multiple ionization de excites. Simultaneous single ionization in the K-shell and multiple ionization in the L-shell gives rise to K α X-ray satellites. These can be studied only by high energy resolution instruments like crystal spectrometry. Experimental investigations were carried out in this field by several workers using photon, electron, and ion excitation modes. The theoretical models to predict their energies and intensities were developed. And also this work can show a clear discrepancy between theoretical and experimental results in the case of satellites formation from different shells. In case of experimental instrumentation, WDXRF is the most accurate for determining the energy and intensity of X-ray satellites. The basic source of data was literature done by different scholars.